2016
DOI: 10.1098/rspb.2015.2359
|View full text |Cite
|
Sign up to set email alerts
|

The social and ecological costs of an ‘over-extended' phenotype

Abstract: Extended phenotypes offer a unique opportunity to experimentally manipulate and identify sources of selection acting on traits under natural conditions. The social cichlid fish Neolamprologus multifasciatus builds nests by digging up aquatic snail shells, creating an extended sexual phenotype that is highly amenable to experimental manipulation through addition of extra shells. Here, we find sources of both positive sexual selection and opposing natural selection acting on this trait; augmenting shell nests in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 35 publications
(50 reference statements)
1
39
1
Order By: Relevance
“…; Jordan et al. ). These studies generally show directional female preferences for exaggerated condition‐dependent structures that reflect male quality (Borgia ; Jordan et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Jordan et al. ). These studies generally show directional female preferences for exaggerated condition‐dependent structures that reflect male quality (Borgia ; Jordan et al.…”
Section: Discussionmentioning
confidence: 99%
“…These studies generally show directional female preferences for exaggerated condition‐dependent structures that reflect male quality (Borgia ; Jordan et al. ). Previous studies of nest building in sticklebacks have found that aspects of nest structure (including nest compactness) are condition‐dependent (Stanley ; Wootton , ; Barber et al.…”
Section: Discussionmentioning
confidence: 99%
“…Neolamprologus multifasciatus is one of the smallest cichlid species in Lake Tanganyika [17] and forms stable social groups consisting of up to ~20 individuals, with one to three adult males, up to five adult females, and the rest being juveniles and immature offspring [14,18]. N. multifasciatus are mostly found living on large shell beds, made almost exclusively of empty N. tanganyicense snail shells that they use as both shelters from predators and as brood chambers for females to lay their eggs and tend to their larvae.…”
Section: Study Speciesmentioning
confidence: 99%
“…The choice of which shells to occupy represents the first step in the process of niche construction at the individual level, producing shelters that individual N. multifasciatus must actively excavate and maintain, and also at the community level, creating structured shell beds on which numerous other species live -this is why the digging behaviour of shell-dwelling cichlids in general has also been referred to as 'ecosystem engineering' [13]. The environmental modifications associated with shell digging have clear fitness consequences for the excavating fish and may also have secondary effects when larger heterospecifics take the shells from smaller shell-dwelling N. multifasciatus [14], suggesting that larger species are too big to clear out shells of internal sediment themselves, and need to forcefully take shells from smaller 'producer' species.…”
Section: Introductionmentioning
confidence: 99%
“…. Moreover, the nest may be more reliable as an extended phenotype if maintenance costs are high (Jordan et al, 2016), but less so if there is a risk that other individuals take over the nest (Bisazza & Marconato, 1988). Given such variation in the relevant costs and benefits, female mate choice may optimally draw from multiple independent cues (Bro-Jørgensen, 2010;Candolin, 2003).…”
mentioning
confidence: 99%